Evaluation of Active Public Green Open Space Service Quality and Provision in Peri-Urban Areas: (Case Study: Dau, Karangploso, Pakis, and Singosari Districts, Malang Regency) - Setyono, Deni Agus; Hasyim, Abdul Wahid; Suharyadi; Hizbaron, Dyah Rahmawati (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2025)
The rapid expansion of built-up areas in Malang Regency has led to a decline in the availability of active public green open space (GOS), creating an imbalance between ecological needs and urban development pressures. This study assesses the provision requirements and service quality of such spaces in four peri-urban districts: Dau, Karangploso, Pakis and Singosari. GOS provision standards were evaluated against the Ministry of Agrarian Affairs and Spatial Planning Regulation No. 14/2022, while service quality was analyzed using Importance Performance Analysis and the Mean Score Analysis, utilizing survey responses from 237 park users. The results demonstrate that none of the districts meet the minimum requirement of 20 percent of their area allocated to public green open spaces. The most significant development potential is concentrated in land parcels exceeding 144,000 m2, totalling 2,702.23 ha, which could be developed into neighborhood-, district-, or city-scale parks. Regarding the service quality, Dau district recorded the highest level of conformity (79.60%), followed by Karangploso (74.62%), Singosari (70.41%), and Pakis (67.09%). Prioritized improvements are necessary for the comfort aspect, cleanliness aspect, lighting aspect, and user facilities aspect. Overall, while the community perceives active public GOS as highly important, the current level of service is inadequate, highlighting the urgent need for robust policies to provide and manage GOS in order to maintain sustainable urban development.